Native aortic coarctation stenting in patients ≥ 46 years old - Szkutnik, Małgorzata; Sulik, Sylwia; Fiszer, Roland; Chodór, Beata; Głowacki, Jan; Białkowski, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction : Stent implantation is an effective therapy for aortic coarctation (CoA) in adolescents and adults. Aim : To present a unique group of patients with native coarctation of the aorta older than or equal to 46 years treated with bare metal or covered stents. Material and methods : Since 2002 we have performed stent implantations by applying bare metal stents or covered stents using femoral access in 24 patients aged 46 and older. Results : We used the Mullins technique in all cases, implanting different stents: Palmaz, Cheatham-Platinum (CP), covered CP or Andrastents XL/XXL. Twenty-one procedures were elective and 3 were urgent. Eighteen bare metal stents (2 stents in one patient) and 7 covered stents were used. All procedures were effective (CoA gradient reduced < 20 mm Hg), despite 2 migrations of bare metal stents. Mean gradient was reduced from 50.6 ±15.3 to 6.8 ±6.5 mm Hg (p < 0.001) and mean lumen diameter of stenosed aorta increased from 5.5 ±2.5 to 14.9 ±5.2 mm (p < 0.001). One special case is discussed – a 49-year-old man with end staged heart failure and severe CoA, who underwent a rescue procedure with a bare metal stent. One serious complication – stroke of the central nervous system – was observed in a 53-year-old woman during covered stent implantation (symptoms resolved during rehabilitation process). Conclusions : Stent implantation of native coarctation of the aorta is also a safe procedure in the eldest patients and is associated with persistent relief of aortic obstruction.